Research of ontology model of heading face - YAO Huiting; CHEN Lichao; PAN Lihu (Gong-kuang zidonghua, 2015)
The paper pointed out that building ontology model of heading face was an important step towards the construction of intelligent decision-making system based on deep analysis of production model of the heading face, obtained relationship between the staff, devices and environment of underground heading face by analyzing factors of mine production safety, and built safety production ontology model of the heading face. Hazardous workplace was taken as an example to simply verify the validity of construction method of the ontology model of heading face.